Evaluating the Interrelationship Between Salivary Cortisol and Glycemia in Type 2 Diabetics - Tharani Vijaya Kumar; Vinoth Vasanthi; Thayalan Dinesh Kumar; Madhu Narayan; Bose Divya; Raj Kumar Krishnan; Ramya Ramadoss (Wolters Kluwer Medknow Publications, 2022)
Introduction: Diabetes mellitus is a multifactorial metabolic condition marked by high blood sugar levels as well as problems with carbohydrate, lipid, and protein metabolism. Impaired insulin secretion and hepatic gluconeogenesis cause high blood sugar levels. Cortisol in the saliva is the unbound, free hormone, with absolute quantities between 30% and 50% fewer than in blood. The aim of the study was to evaluate the levels of salivary cortisol in normal healthy controls and type 2 diabetics. The objective was to evaluate the morning and evening levels of salivary cortisol in normal and type 2 diabetics by enzyme-linked immunosorbent assay (ELISA). Materials and Methods: 20 patients in the age group of 30 to 60 years with type 2 diabetes with HbA1c <6.5% were included in Group I. Twenty participants in the age group of 30 to 60 years were included in Group II. Salivary samples were collected and centrifuged at -4°C at 3500 rpm and ELISA was performed. Data were analyzed using Statistical Package for the Social Sciences version software version 16. Paired sample t test was used. Results: The mean morning salivary cortisol level of diabetic patients (Group I) was 1.62 mmol/dL and the evening was 1.34 mmol/dL. The difference was statistically significant (P = 0.00001). The mean salivary cortisol level of healthy subjects in the morning was 0.47 mmol/dL and evening was 0.29 mmol/dL, which is statistically significant (P = 0.00001). Conclusion: From this study, we can conclude that the salivary cortisol level is increased in patients with type 2 diabetes when compared to healthy individuals. There are no obvious changes in morning and evening salivary cortisol levels of diabetes patients.